The Dialogue between Islam and the West: Challenges and Strategies for Coexistence - Klaina, Mekki (International Journal of Humanities, Education, and Social Sciences, 2025)
Coexistence among nations and peoples cannot be achieved in a context of isolation and avoidance of dialogue with others, whether at the individual, group, institutional, or state level. Dialogue helps to bridge perspectives and remove misunderstandings. While some speak of a "clash of civilizations," this notion arises from certain entrenched mindsets. A better approach would be to advocate for a "dialogue of civilizations," especially in a world fraught with violence and the collapse of traditional governance systems. Dialogue is vital, as it is a means of bringing peoples closer together. It is beneficial to understand the West's perspective on the Islamic world, as understanding the other's stance is essential. It is equally important to allow the other to know you, rather than forming prejudiced judgments that can lead to misunderstandings, potentially escalating to violence and war. This war could have been avoided if both parties had listened to each other and engaged in dialogue. This leads us to explore the reasons behind the existing tension and suggest practical means and a working strategy to bridge gaps between peoples. This study uses a descriptive and analytical approach to the current situation and history, based on facts and documents. The research findings indicate that the existing differences between the Islamic and Western worlds are due to negative perceptions of each other. Therefore, this study identifies several means to achieve coexistence, such as educational curricula, promoting the values of dialogue and acceptance of the other, avoiding double standards, and working on institutionalized dialogue.